A preoperative nomogram for sepsis in percutaneous nephrolithotomy treating solitary, unilateral and proximal ureteral stones - Xun,Yang; Yang,Yuanyuan; Yu,Xiao; Li,Cong; Lu,Junlin; Wang,Shaogang (PeerJ, 2020)
Background Postoperative sepsis is a lethal complication for percutaneous nephrolithotomy (PCNL). An early predictive model combined local and systemic conditions is urgently needed to predict infectious events. We aim to determine the preoperative predictors of sepsis after PCNL in patients with unilateral, solitary, and proximal ureteral stones. Methods A total of 745 patients who underwent PCNL between January 2012 and December 2018 were retrospectively enrolled. Sepsis was defined based on the International Sepsis Definitions in 2001, and the preoperative factors were compared between the non-sepsis and sepsis groups. Univariable analysis and multivariable logistic regression analysis were conducted to determine the predictors for sepsis after PCNL. A nomogram was generated using the predictors. Results In this study, 35 patients (4.7%) developed sepsis after PCNL. Univariate analysis showed that post-PCNL sepsis was associated with the female, lower albumin, higher globulin, lower albumin globulin ratio (AGR < 1.5), preoperative fever, leukocytosis (WBC ≥ 10,000 cells/μL), positive urine culture, leukocyturia (≥50 cells/μL) and positive urine nitrite. Multivariate logistic regression analysis suggested that AGR < 1.5 (odds ratio [OR] = 5.068, 95% confidence interval [CI] [1.135–22.624], P = 0.033), positive urine culture (OR = 3.243, 95% CI [1.162–9.047], P = 0.025), leukocytosis (OR = 3.706, 95% CI [1.444–9.512], P = 0.006) and female (OR = 2.529, 95% CI [1.127–5.672], P = 0.024) were independent risk factors for sepsis. A nomogram was generated and displayed favorable fitting (Hosmer–Lemeshow test P = 0.797), discrimination (area under receiver operating characteristic curve was 0.807), and clinical usefulness by decision curve analysis. Conclusions Patients with certain preoperative characteristics, such as female, lower AGR, positive urine culture, and leukocytosis, who undergo PCNL may have a higher risk of developing sepsis. A cautious preoperative evaluation and optimized treatment strategy should be considered in these patients to minimize infectious complications.
Keywords: Percutaneous nephrolithotomy; Infection; Nomogram; Urolithiasis; Albumin globulin ratio